Breast Feeding as Analgesia in Neonates: A Randomized Controlled Trial - Singh, Rajesh Kumar; Simalti, Ashish Kumar; Singh, Daljit (Journal of Nepal Paediatric Society, 2017)
Introduction: Major myth regarding neonatal pain suggests that neonates because of their neurological immaturity do not experience pain. Although exact mechanism is not known, it is proposed that breast feeding through combination of various senses and the closeness of the infant’s mother, saturates the senses thus reducing perception of noxious stimuli. The objective of this study was to investigate the analgesic effect of breastfeeding during blood sampling through heel lance in healthy term neonates. Material and Methods: This was a Randomized controlled trial done in a Tertiary level Neonatal Intensive Care Unit. Sixty healthy term newborns, undergoing heel prick were included in study. Neonates were randomly assigned to two groups: Group I (breastfed) with; Group II (not breast fed). Babies were given heel prick and crying time, Heart rate, SpO2 and BP monitored. Changes in various physiological parameters following a heel prick were studied in two groups. Results: Neonates in both groups expressed pain by crying, increase in heart rate, fall in transcutaneous oxygen saturation and rise in blood pressure. Compared to control group, the babies who were breast fed were found to have lesser crying time (40.04 sec and 69.09 sec respectively, p<0.05) and lesser rise in heart rate (rise of 21.78 and 34.46 bpm respectively, p<0.03). In the breast fed group there was a trend to a lesser decrease in oxygen saturation and lesser rise in blood pressure though this was not statistically significant. Conclusion: Breast feeding offers a quick and effective means of reducing pain in neonates during routine neonatal procedures. J Nepal Paediatr Soc 2016;36(3):238-242